Student Character Grouping Based on Six Dimensions of Pancasila Student Profile Using Clustering Method (Case Study of SMK Swasta Setia Budi Binjai) - Zuliani, Zuliani; Ramadani, Suci; Buaton, Relita (International Journal of Informatics, Economics, Management and Science, 2023)
Character education is one of the important aspects in developing students into individuals with integrity, ethics, and responsibility. Pancasila as the foundation of the Indonesian state has a central role in shaping students' character. This study aims to categorize student character based on six dimensions of the Pancasila learner profile at SMK Swasta Setia Budi Binjai. The six dimensions of the Pancasila learner profile that are the focus of this study include: 1) Faithful, Devoted to God Almighty and Noble, 2) Global Diversity, 3) Mutual Cooperation, 4) Independent, 5) Creative, 6) Critical Reasoning. The clustering method is used to group students based on the Pancasila learner profile measured through questionnaires distributed to subject teachers. The collected data will be analyzed using relevant clustering algorithms to identify the pattern of student characters present in the school population. This research is expected to provide deeper insight into the character of students at SMK Swasta Setia Budi Binjai based on Pancasila values. The results of this study are expected to be the basis for the development of a more effective character education program that focuses on strengthening the values of Pancasila in an effort to produce a young generation with strong character, love for the country, and contribute positively to society and the nation.